'Acoustic shock': A new occupational disease? Observations from clinical and medico-legal practice. (October 2014) - Parker, William; Parker, Victoria; Parker, Glynn; Parker, Andrew
Abstract Objective: 'Acoustic Shock' injury has arisen with the proliferation of telephone-based employment but is not yet fully understood. This study aimed to further characterize this phenomenon by reviewing the current literature and analysing a case series. Design: Cases were identified from medicolegal and clinical practice. Case notes, including General Practitioner and occupational health records where available, were scrutinised and information on demographics and medical history obtained. Patients underwent interview, examination, and pure-tone audiometry. Study sample: Thirty cases were included. Eighteen (60%) were female. Mean age was 41.6 years. Results: There was a range of otological symptoms (mean 3.2 per patient), most commonly tinnitus which was present in 27 (90%), accompanied by diverse non-otological symptoms. Twenty-one (70%) had previous oto-pathology, 19 (63%) psychopathology, and five (17%) head injury. Examination was normal in 28 (93%), as was audiometry in 13 (43%). Eleven (50%) smoked. Hearing loss was not necessarily a feature. Conclusions: The condition known as 'acoustic shock' injury is a complex disorder producing a range of symptoms with psychological overlay. However, there is often little clinical evidence of pathology and it has not been adequately defined as yet. By further characterization, epidemiology and aetiology can be better understood.